Algae Drive Enhanced Darkening of Bare Ice on the Greenland Ice Sheet. Issue 22 (18th November 2017) - Stibal, Marek; Box, Jason E.; Cameron, Karen A.; Langen, Peter L.; Yallop, Marian L.; Mottram, Ruth H.; Khan, Alia L.; Molotch, Noah P.; Chrismas, Nathan A. M.; Calì Quaglia, Filippo; Remias, Daniel; Smeets, C. J. P. Paul; et al.
Abstract: Surface ablation of the Greenland ice sheet is amplified by surface darkening caused by light‐absorbing impurities such as mineral dust, black carbon, and pigmented microbial cells. We present the first quantitative assessment of the microbial contribution to the ice sheet surface darkening, based on field measurements of surface reflectance and concentrations of light‐absorbing impurities, including pigmented algae, during the 2014 melt season in the southwestern part of the ice sheet. The impact of algae on bare ice darkening in the study area was greater than that of nonalgal impurities and yielded a net albedo reduction of 0.038 ± 0.0035 for each algal population doubling. We argue that algal growth is a crucial control of bare ice darkening, and incorporating the algal darkening effect will improve mass balance and sea level projections of the Greenland ice sheet and ice masses elsewhere. Plain Language Summary: Melting of the Greenland ice sheet is enhanced by surface darkening caused by various impurities. We quantified the contribution of dark pigment‐producing algae to the ice sheet surface darkening, based on field measurements in the southwestern part of the ice sheet during the 2014 melt season. Our analysis reveals that the impact of algae on bare (snow‐free) ice darkening was greater than that of other impurities and, therefore, that algal growth was a crucial control of bare ice darkening in the study area. Incorporating the darkening effect of algal growth is expected to improve future projections of the Greenland ice sheet melting. Key Points: We present the first quantitative assessment of the algal contribution to the Greenland ice sheet surface darkening We found that the effect of algae on bare ice darkening in the study area is greater than that of nonalgal impurities Incorporating the darkening effect of ice algal growth will improve mass balance and sea level projections of the Greenland ice sheet